Stochastic motion of noble gases on a graphene sheet - Neek-Amal, M.; Lajevardipour, A. (Elsevier, 2010)
The stochastic motion of noble gases in a periodic two-dimensional potential produced by a graphene sheet is studied. We calculate the depth of the potential well of the interaction between noble gases and the graphene sheet. The Langevin equation is solved numerically to explain the effects of the binding energy, coefficient of friction and the equilibrium distance to the motion of noble gases on the graphene sheet. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Stochastic motion; Graphene sheet; Noble gases; Langevin dynamics